2016
DOI: 10.14777/uti.2016.11.3.103
|View full text |Cite
|
Sign up to set email alerts
|

Serum CCL11 Levels in Benign Prostatic Hyperplasia and Prostate Cancer

Abstract: Purpose: CC-chemokine ligand 11 (CCL11; eotaxin-1), an eosinophil chemoattractant chemokine, has been proposed as a serum marker for prostate cancer (PCa) by two research groups. We investigated the usefulness of CCL11 in diagnosing prostatic diseases, such as benign prostatic hyperplasia (BPH) and PCa. Materials and Methods: CCL11 was measured in the sera of 139 men with BPH, 44 men with PCa, and 45 control men attending an outpatient health-screening clinic. A commercial enzyme-linked immunosorbent assay kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Sera were obtained from 139 patients with BPH, 44 with prostate cancer and 58 male healthy volunteers (mean age: 40.4±0.15) who visited Hanyang University International Hospital Health Promotion Center. Healthy volunteers had no history of prostatic disease [14]. Blood samples of 7 ml were collected, and plasma was stored at −70°C.…”
mentioning
confidence: 99%
“…Sera were obtained from 139 patients with BPH, 44 with prostate cancer and 58 male healthy volunteers (mean age: 40.4±0.15) who visited Hanyang University International Hospital Health Promotion Center. Healthy volunteers had no history of prostatic disease [14]. Blood samples of 7 ml were collected, and plasma was stored at −70°C.…”
mentioning
confidence: 99%
“…35,36 CCL11, CCL18, and MMP-7, in combination with CA125 can be used for the diagnosis of epithelial ovarian cancer. 37 Kim et al 38 indicated that CCL11 might be helpful in the diagnosis of prostate cancer. It was shown that the expression of CHRDL1 was associated with the clinical outcomes in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%